Preparation method and application of modified zero-valent copper catalyst

The zero-valent copper catalyst is modified by oxalic acid combined with ball milling technology to improve its activity and stability, and the catalyst is recovered and reused by combining with sponge. The problems of complex preparation process and difficult material recycling in the prior art are solved, and efficient degradation and environmentally friendly sewage treatment effect are achieved.

CN119897161APending Publication Date: 2025-04-29UNIV OF JINAN
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510057912.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The preparation process of existing modified zero-valent copper catalysts is complicated, and the materials are difficult to recover in wastewater treatment, resulting in secondary pollution problems.

Method used

The zero-price copper is treated with oxalic acid combined with ball milling technology to increase the proportion of low-price copper in the catalyst, regulate the generation of singlet oxygen, and prepare melamine sponge-based floats by combining it with a sponge to achieve the recovery and reuse of the catalyst.

Benefits of technology

It improves the activity and stability of the catalyst, can effectively degrade a variety of organic matter within a wide pH range, solves the problem of difficulty in material recycling, and reduces the secondary pollution of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119897161A_ABST
    Figure CN119897161A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method and application of a modified zero-valent copper catalyst, and belongs to the technical field of advanced oxidation catalytic materials for sewage treatment. In the process of researching modified zero-valent copper, the inventor finds that the proportion of low-valent copper in the catalyst can be increased by treating zero-valent copper by using oxalic acid in combination with a ball milling technology for the first time; the charge distribution of copper is changed, and the generation way of singlet oxygen can be regulated and controlled, so that the activity of the catalyst is higher; the prepared modified zero-valent copper catalyst is combined with sponge to prepare the melamine sponge-based floating body, so that the catalyst can be recycled, the problem that materials are difficult to recycle in sewage treatment can be solved, and the secondary pollution of the catalyst is obviously reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of advanced oxidation catalytic materials for sewage treatment, and specifically relates to a preparation method of a modified zero-valent copper catalyst and application thereof. Background Art

[0002] The safety issues caused by the presence of difficult-to-degrade and new organic pollutants to surface water or groundwater have attracted more and more attention. Compared with other oxidants in advanced oxidation technology, molecular oxygen (O2) has the advantages of being green, abundant in reserves, sustainable, environmentally friendly, and widely applicable. In view of this, activated O2 technology has important application potential and advantages in the field of water treatment. It cannot directly oxidize organic matter due to the spin-forbidden effect, so various O2 activation technologies have emerged.

[0003] Activated O2 can produce a variety of active species. However, the free radical-dominated reaction system is sensitive to natural organic matter and various anions in wastewater, and is easily quenched by them, thus seriously inhibiting the reaction activity. In contrast, the non-free radical reaction mediated by singlet oxygen can overcome the inherent shortcomings of free radicals, has significant tolerance to complex matrices and inorganic ions in water, and has a relatively long lifespan. Therefore, it is particularly important to regulate the generation of singlet oxygen.

[0004] Nowadays, zero-valent metals are commonly used to activate O2, such as zero-valent iron (ZVI), zero-valent aluminum (ZVAl), and zero-valent copper (ZVC). Compared with other zero-valent metals, ZVC has the advantages of being relatively stable, not easy to passivate, and applicable to a wider pH range, but its own catalytic effect is limited, there are fewer active sites, and it is easy to agglomerate during the preparation process. Therefore, many researchers choose to modify ZVC with other materials to enhance its stability and effective activity.

[0005] Currently, there are many ways to modify ZVC, such as doping, loading, and modification, but the material preparation process is relatively complicated and the quantity is small, which is not conducive to industrial use. Summary of the invention

[0006] In view of the deficiencies in the prior art, the present invention provides a preparation method of a modified zero-valent copper catalyst and application thereof.

[0007] In the process of studying modified zero-valent copper, the inventors discovered for the first time that using oxalic acid combined with ball milling technology to treat zero-valent copper can increase the proportion of low-valent copper in the catalyst, change the charge distribution of copper, and regulate the generation pathway of singlet oxygen, making the catalyst more active.

[0008] The present invention also utilizes the prepared modified zero-valent copper catalyst in combination with a sponge to prepare a melamine sponge-based floating body, which is beneficial to the recovery and reuse of the catalyst, can solve the problem of difficult material recovery in sewage treatment, and significantly reduces the secondary pollution of the catalyst.

[0009] The technical solution of the present invention is as follows:

[0010] A method for preparing a modified zero-valent copper catalyst comprises the following steps:

[0011] The zero-valent copper powder and oxalic acid are uniformly mixed to obtain a mixture, which is ball-milled using zirconium oxide balls. The obtained material is washed, centrifuged, and dried to obtain a modified zero-valent copper catalyst.

[0012] Preferably according to the present invention, in the above method, the mass ratio of the grinding balls to the mixture is (50-150):(3.5-4.5), the ball milling time is 1-4 hours, and the rotation speed is 450-550 rpm.

[0013] Further preferably, in the above method, the mass ratio of the grinding balls to the mixture is 100:(3.5-4.5), the ball milling time is 2 hours, and the rotation speed is 500 rpm.

[0014] Preferably according to the present invention, in the above method, the oxalic acid is oxalic acid dihydrate.

[0015] Further preferably, in the above method, the ratio of the amount of oxalic acid dihydrate to the amount of zero-valent copper substance is (0.005-0.04):1.

[0016] More preferably, in the above method, the ratio of the amount of oxalic acid dihydrate to the zero-valent copper substance is 0.02:1.

[0017] Preferably according to the present invention, in the above method, the washing process uses distilled water and anhydrous ethanol for washing in sequence, and the drying method is vacuum drying at 60-80°C.

[0018] Further preferably, the washing process uses distilled water and anhydrous ethanol for 3 to 5 times respectively.

[0019] A melamine sponge-based floating body comprises the modified zero-valent copper catalyst prepared by the above method and melamine sponge.

[0020] The method for preparing the above-mentioned melamine sponge-based floating body comprises the following steps:

[0021] Step S1, placing a melamine sponge in a mixture of dopamine hydrochloride and TRIS buffer, ultrasonically treating the sponge, transferring the sponge to an oscillator for treatment after ultrasonication, and then washing and drying the sponge for later use;

[0022] Step S2, uniformly mixing the modified zero-valent copper catalyst prepared by the above method with distilled water to form a dispersion, soaking the melamine sponge treated in step S1 in the dispersion, then taking out the melamine sponge and drying it, repeating this process more than once to obtain a melamine sponge-based floating body.

[0023] Preferably according to the present invention, in step S1, the concentration of dopamine hydrochloride in the mixed solution is (1.5-2.5) g / L, and the amount of TRIS buffer in every 100 ml of the mixed solution is 1-2 ml.

[0024] Further preferably, in the above method, the concentration of dopamine hydrochloride is 2 g / L, and the amount of TRIS buffer in every 100 ml of the mixed solution is 1 ml.

[0025] Preferably according to the present invention, in step S1, the length, width and height of the melamine sponge are (1-2) cm×(1-2) cm×(1-2) cm respectively, the oscillator rate is 145-155 times / minute, and the oscillation time is 11-12 hours.

[0026] Further preferably, in the above method, the melamine sponge has a length, width and height of 2 cm×2 cm×2 cm respectively, the oscillator rate is 150 times / minute, and the oscillation time is 12 hours.

[0027] Preferably according to the present invention, in step S2, the concentration of the modified zero-valent copper catalyst in the dispersion is 4-5 g / L.

[0028] Further preferably, in step S2, the concentration of the modified zero-valent copper catalyst in the dispersion is 5 g / L.

[0029] Preferably according to the present invention, in step S2, the melamine sponge is soaked for 10 to 20 minutes.

[0030] Preferably according to the present invention, in step S2, the drying method is drying at 60-80°C.

[0031] Application of the modified zero-valent copper catalyst prepared by the above method or the above melamine sponge-based floating body in degrading organic pollutants.

[0032] Preferably, according to the present invention, the modified zero-valent copper catalyst or melamine sponge-based floating body prepared by the above method is used in degrading organic pollutants in wastewater.

[0033] Preferably according to the present invention, the organic pollutants include oxytetracycline, tetracycline, rhodamine B, methylene blue and p-nitrophenol.

[0034] The beneficial effects of the present invention include at least the following:

[0035] 1. The present invention discovers for the first time that using oxalic acid combined with ball milling technology to treat zero-valent copper can increase the proportion of low-valent copper in the catalyst, change the charge distribution of copper, and regulate the generation pathway of singlet oxygen, thereby making the catalyst more active.

[0036] 2. The modified zero-valent copper catalyst prepared by the present invention pre-treats the zero-valent copper with oxalic acid by ball milling, and the amount of oxalic acid and zero-valent copper added is regulated. The inventors found that the modified zero-valent copper catalyst prepared when the ratio of the amount of oxalic acid dihydrate to the amount of zero-valent copper substance is 0.02:1 has a better effect.

[0037] 3. The method provided by the present invention has readily available raw materials, a simple preparation method, can be mass-produced, and has a wide range of applications, which is conducive to the application of modified zero-valent copper catalysts in actual sewage treatment.

[0038] 4. The modified zero-valent copper catalyst prepared by the present invention has a good catalytic effect in a wide pH range and can degrade a variety of organic matter.

[0039] 5. The preparation method of the melamine sponge-based floating body provided by the present invention combines the modified zero-valent copper catalyst powder with the sponge. In the actual treatment of water bodies, it is beneficial to recover and reuse the catalyst, which can solve the problem of difficult material recovery in sewage treatment and significantly reduce the secondary pollution of the catalyst. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 This is a SEM image of the Ox-ZVC catalyst prepared in Example 1 of the present invention.

[0041] Figure 2 The XRD diagrams of the Ox-ZVC catalyst prepared in Example 1 of the present invention and the B-ZVC catalyst and ZVC prepared in Comparative Example 1 are shown.

[0042] Figure 3 The XPS graphs and the proportions of copper in different valence states of Ox-ZVC and B-ZVC prepared in Example 1 and Comparative Example 1 of the present invention are shown.

[0043] Figure 4 The EPR spectra of singlet oxygen generated by Ox-ZVC and B-ZVC prepared in Example 1 and Comparative Example 1 of the present invention.

[0044] Figure 5 It is a comparison chart of the quenching experiments of Ox-ZVC and B-ZVC prepared in Example 1 of the present invention and Comparative Example 1.

[0045] Figure 6 The DPA degradation UV spectra of Ox-ZVC and B-ZVC prepared in Example 1 and Comparative Example 1 of the present invention are shown.

[0046] Figure 7 The singlet oxygen generation mechanism diagram of Ox-ZVC and B-ZVC prepared in Example 1 and Comparative Example 1 of the present invention.

[0047] Figure 8 The figure is a comparison chart of the degradation effect of the Ox-ZVC catalyst prepared in Example 1 of the present invention and different catalysts on oxytetracycline.

[0048] Fig. 9 The figure is a comparison chart of the degradation effect of the Ox-ZVC catalyst prepared in Example 1 of the present invention on oxytetracycline at different pH values.

[0049] Fig.10 The figure shows the effect of Ox-ZVC catalyst prepared with different proportions of oxalic acid on the degradation of OTC.

[0050] Fig.11 The figure is a comparison chart of the degradation effects of the Ox-ZVC catalyst prepared in Example 1 of the present invention on different pollutants.

[0051] Fig.12 Schematic diagram and SEM image of the melamine sponge-based floating body prepared in Example 5 of the present invention.

[0052] Fig.13 This is a diagram of a long-term experimental device for a melamine sponge-based floating body prepared in Example 5 of the present invention.

[0053] Fig.14 This is a diagram showing the degradation effect of oxytetracycline in a long-term experiment using the melamine sponge-based floating body prepared in Example 5 of the present invention. DETAILED DESCRIPTION

[0054] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention is described in detail below with reference to the accompanying drawings and specific embodiments, but the protection scope of the present invention is not limited thereto.

[0055] The contents not described in detail in the embodiments are based on the prior art in the art.

[0056] H2C2O4·2H2O was purchased from Tianjin Damao Chemical Reagent Factory, and ZVC, dopamine hydrochloride, and TRIS buffer were purchased from Shanghai MacLean Reagent Co., Ltd.

[0057] Example 1

[0058] A method for preparing a modified zero-valent copper catalyst comprises the following steps:

[0059] S1. Weigh 4.0317 g of ZVC, 0.16 g of H2C2O4·2H2O (the ratio of dihydrate oxalic acid to zero-valent copper is 0.02:1), and 100 g of zirconia balls (the diameter of the zirconia balls is 6 mm), place them in a ball mill, set the ball milling time to 2 hours, and the speed to 500 rpm; after the ball milling is completed, wash the material with distilled water and anhydrous ethanol for 3 times respectively, and then dry it in a vacuum oven at 60°C for 12 hours to obtain a modified zero-valent copper (Ox-ZVC) catalyst.

[0060] In order to explore the degradation rate of oxytetracycline (OTC) by the Ox-ZVC catalyst prepared in this example, a degradation test was performed using the following method: at room temperature, 500 mg / L of the catalyst was mixed with 10 mg / L of an OTC solution, the pH of the mixture was adjusted to 7.0±0.1 with sodium hydroxide and hydrochloric acid, and then aeration was performed to start the degradation experiment. The experiment was carried out under magnetic stirring conditions, and the absorbance of the solution was measured at a wavelength of 355 nm using an ultraviolet spectrophotometer. The results showed that after 90 minutes of reaction, the OTC degradation rate reached 82.2%.

[0061]

[0062] Where C is the absorbance of OTC at a certain reaction time, and C0 is the absorbance of initial OTC.

[0063] Comparative Example 1

[0064] A method for preparing a ball-milled zero-valent copper (B-ZVC) catalyst comprises the following steps:

[0065] S1. Weigh 4.1917 g of ZVC and 100 g of zirconia balls (the diameter of the zirconia balls is 6 mm), place them in a ball mill, set the ball milling time to 2 hours, and the rotation speed to 500 rpm; after the ball milling is completed, wash the material with distilled water and anhydrous ethanol for 3 times respectively, and then dry it in a vacuum oven at 60° C. for 12 hours to obtain a ball-milled zero-valent copper (B-ZVC) catalyst.

[0066] In order to explore the degradation rate of OTC by B-ZVC catalyst, the same method as in Example 1 was used for detection.

[0067] The results show that after 90 minutes of reaction, the degradation rate of OTC by the B-ZVC catalyst is 52.6%, indicating that the degradation rate of OTC by the Ox-ZVC catalyst prepared in Example 1 is improved to a certain extent compared with the B-ZVC catalyst prepared in Comparative Example 1.

[0068] Figure 1 Figure 2 is a scanning electron microscope (SEM) image of Ox-ZVC material, from which it can be seen that the catalyst prepared in Example 1 is an irregular sphere. Figure 2 As shown in the XRD diagram, for ZVC and B-ZVC, the peaks at 2θ=43.5, 50.4 and 74.0 correspond to the (111), (200) and (220) crystal planes, respectively (PDF#01-1241). For Ox-ZVC, there is an additional peak at 2θ=36.5 located at the (211) crystal plane compared to ZVC and B-ZVC (PDF#02-1067). It can be seen from the figure that there is no significant difference between B-ZVC and Ox-ZVC in crystal structure. After comparison with the standard card, it is found that the peak is mainly copper. This shows that the main component of the Ox-ZVC catalyst prepared by the present invention is copper. Figure 3 The Cu2pXPS graphs of B-ZVC and Ox-ZVC show that the characteristic peak of copper in Ox-ZVC moves toward the direction of low binding energy, which is 0.1eV smaller than that of B-ZVC, changing the charge distribution of copper. It is also found that the proportion of low-valent copper in Ox-ZVC prepared by the present invention is 72.4%, while the proportion of low-valent copper in B-ZVC is 29.2%, indicating that the proportion of low-valent copper is greatly increased after oxalic acid pretreatment, further improving the activity of the catalyst.

[0069] The Ox-ZVC prepared in Example 1 and the B-ZVC prepared in Comparative Example 1 were characterized by electron paramagnetic resonance. Figure 4 As shown, the inventors found that Ox-ZVC can produce more singlet oxygen. TEMP is 1 O2 quencher, PBQ is ·O2 - Quencher, CAT is H2O2 quencher, TBA is ·OH quencher, according to the quenching results ( Figure 5 ), the active species of B-ZVC and Ox-ZVC are mainly 1 O2. DPA spectrum results ( Figure 6 ) for Ox-ZVC, the addition of quenchers TBA, PBQ and CAT had a significant effect on 1 The production of O2 was inhibited by PBQ, and the inhibitory effect was the strongest, indicating that 1 The production of O2 is mainly related to O2 - The second is H2O2 and ·OH, while TBA and CAT have no inhibitory effect on B-ZVC, indicating that 1 O2 can only be - The results show that the modified zero-valent copper catalyst prepared by the present invention regulates the generation pathway of singlet oxygen, and the specific free radical conversion pathway is as follows Figure 7 .

[0070] At the same time, the degradation of OTC in ZVC / Air, B-ZVC / Air, and Ox-ZVC / Air was also compared (using the same method as in Example 1 for detection). Figure 8 As shown, Figure 8 The results further verified the excellent degradation ability of Ox-ZVC / Air on OTC.

[0071] In addition, in order to explore the catalytic effect of Ox-ZVC prepared in Example 1 at different pH values, the degradation experimental conditions in Example 1 were adopted, but the pH conditions were changed, and the OTC degradation experiments were carried out at pH = 4, 5, 6, 8, 9, and 10. Fig. 9 It can be seen that the degradation effect of Ox-ZVC material is relatively stable in a wide pH range, indicating that Ox-ZVC is not greatly affected by pH in practical applications.

[0072] Example 2

[0073] The difference from Example 1 is that the proportion of oxalic acid is different, specifically, the ratio of the amount of oxalic acid dihydrate to the zero-valent copper substance is 0.005:1, 0.01:1, and 0.04:1, respectively, and the other factors are the same, and Ox-ZVC is obtained respectively.

[0074] In Example 1, the molar ratio of oxalic acid dihydrate to zero-valent copper is 0.02:1.

[0075] According to the method provided in Example 1, the degradation effect of Ox-ZVC obtained by different proportions of oxalic acid was tested. The results are shown in Fig.10 The degradation rate was 65.6% when the oxalic acid ratio was 0.005:1, 69.9% when the ratio was 0.01:1, 82.2% when the ratio was 0.02:1, and 73.1% when the ratio was 0.04:1.

[0076] The Ox-ZVC prepared when the molar ratio of dihydrate oxalic acid to zero-valent copper is 0.02:1 has the best effect in degrading OTC.

[0077] Example 3

[0078] The difference from Example 1 is that the ball-to-mass ratio is different, specifically, the mass ratio of the grinding balls to the mixture is 50:4 and 150:4 respectively, and the other parts are the same, and Ox-ZVC is obtained respectively.

[0079] In Example 1, the mass ratio of the grinding balls to the mixture is 100:4.

[0080] According to the method provided in Example 1, the degradation effect of Ox-ZVC obtained with different spheroid-to-mass ratios on OTC was detected. When the spheroid-to-mass ratio was 50:4, the degradation rate was 74.4%, when it was 100:4, the degradation rate was 82.2%, and when it was 150:4, the degradation rate was 73.7%.

[0081] The Ox-ZVC prepared when the mass ratio of grinding balls to mixture is 100:4 has the best effect in degrading OTC.

[0082] Example 4

[0083] The difference from Example 1 is that the ball milling time is different, specifically, the ball milling time is 1 hour and 4 hours respectively, and the other parts are the same, and Ox-ZVC is obtained respectively.

[0084] The ball milling time in Example 1 is 2 hours.

[0085] The degradation effect of Ox-ZVC obtained by different ball milling times was detected according to the method provided in Example 1. The degradation rate was 60.6% when the ball milling time was 1 hour, 82.2% when the ball milling time was 2 hours, and 73.5% when the ball milling time was 4 hours.

[0086] Ox-ZVC prepared with a ball milling time of 2 hours has the best effect in degrading OTC.

[0087] Effect Example 1

[0088] In order to explore the degradation effects of the Ox-ZVC prepared in Example 1 and the B-ZVC prepared in Comparative Example 1 on different pollutants, the degradation experimental conditions of Example 1 were used to perform degradation tests on oxytetracycline (OTC), tetracycline (TC), rhodamine B (RhB), methylene blue (MBT), and p-nitrophenol (PNP). The test results are as follows: Fig.11 As shown, from Fig.11 It can be seen that the degradation rates of Ox-ZVC for OTC, TC, RhB, MBT and PNP are 82.2%, 86.7%, 71.2%, 48.5% and 54.3%, respectively. The degradation rates of B-ZVC for OTC, TC, RhB, MBT and PNP are 52.6%, 63.2%, 50%, 16% and 23.1%, respectively. The above experimental results show that the removal effect of Ox-ZVC on various pollutants is stronger than that of B-ZVC. During the experiment, the reaction time can be appropriately extended to improve the catalytic efficiency of MBT and PNP.

[0089] Example 5

[0090] A method for preparing a melamine sponge-based floating body comprises the following steps:

[0091] S1. Weigh 0.2g dopamine hydrochloride and 100ml distilled water into a beaker, add 1ml TRIS buffer, put in a 2cm×2cm×2cm melamine sponge and sonicate until brown. After sonication, transfer to an oscillator, set the oscillation frequency to 150 times / min, and the oscillation time to 12 hours. After the reaction is completed, wash the sponge three times with distilled water, and then dry the melamine sponge at 80℃ for later use.

[0092] S2. Weigh 0.5 g of the Ox-ZVC catalyst powder prepared in Example 1 and 100 ml of distilled water, mix them evenly to form a dispersion, and place the melamine sponge treated in step S1 in the dispersion; soak the sponge for 20 minutes, and then dry it at 80° C., repeat three times to obtain a melamine sponge-based floating body.

[0093] Fig.12 This is a SEM comparison of melamine sponge before and after loading. Fig.12 It can be seen that the sponge not loaded with Ox-ZVC catalyst is relatively smooth, while the sponge loaded with Ox-ZVC catalyst is significantly different from it.

[0094] In particular, the present invention also studies the potential application of the above-mentioned melamine sponge-based floating body in water treatment and establishes a continuous flow reactor. Fig.13 The device diagram is shown in Figure 1. A pollutant OTC was selected for degradation experiment and operated continuously for 30 hours. Fig.14 It can be seen that the OTC degradation efficiency was stable at more than 75% during the period, indicating that the material has good stability, indicating that the melamine sponge-based floating body has significant potential in practical water purification applications.

[0095] The modified zero-valent copper catalyst prepared by the present invention has a high proportion of low-valent copper, can produce more singlet oxygen, and regulates the generation pathway of singlet oxygen, so the catalyst has higher activity; it has a good catalytic effect in a wider pH range and can degrade a variety of organic matter.

[0096] The method provided by the present invention has the advantages of readily available raw materials, simple preparation method, mass production, wide application range, and meeting the needs of industrial production, and is conducive to the application of modified zero-valent copper catalyst in actual sewage treatment.

[0097] The melamine sponge-based floating body and preparation method provided by the present invention combine modified zero-valent copper catalyst powder with sponge, which is beneficial to recovering and reusing the catalyst in actual water treatment, can solve the problem of difficult material recovery in sewage treatment, and significantly reduce secondary pollution of the catalyst.

Claims

1. A method for preparing a modified zero-valent copper catalyst, characterized in that: The steps include: The zero-valent copper powder and oxalic acid are uniformly mixed to obtain a mixture, which is ball-milled using zirconium oxide balls. The obtained material is washed, centrifuged, and dried to obtain a modified zero-valent copper catalyst.

2. The method according to claim 1, characterized in that The mass ratio of the grinding balls to the mixture is (50-150):(3.5-4.5), the ball milling time is 1-4 hours, and the rotation speed is 450-550 rpm; Preferably, the mass ratio of the grinding balls to the mixture is 100:(3.5-4.5), the ball milling time is 2 hours, and the rotation speed is 500 rpm.

3. The method according to claim 1, characterized in that Oxalic acid is oxalic acid dihydrate; Preferably, the ratio of the amount of oxalic acid dihydrate to the amount of zero-valent copper substance is (0.005-0.04):1; More preferably, the ratio of the amount of oxalic acid dihydrate to the amount of zero-valent copper substance is 0.02:

1.

4. The method according to claim 1, characterized in that The washing process uses distilled water and anhydrous ethanol for washing in sequence, and the drying method uses vacuum drying at 60-80°C; Preferably, the washing process uses distilled water and anhydrous ethanol for 3 to 5 times respectively.

5. A melamine sponge-based floating body, characterized in that: The invention comprises a modified zero-valent copper catalyst prepared by the method according to any one of claims 1 to 4 and a melamine sponge.

6. The method for preparing the melamine sponge-based floating body according to claim 5, characterized in that: The steps include: Step S1, placing a melamine sponge in a mixture of dopamine hydrochloride and TRIS buffer, ultrasonically treating the sponge, transferring the sponge to an oscillator for treatment after ultrasonication, and then washing and drying the sponge for later use; Step S2, uniformly mixing the modified zero-valent copper catalyst prepared by the method described in any one of claims 1 to 4 with distilled water to form a dispersion, soaking the melamine sponge treated in step S1 in the dispersion, then taking out the melamine sponge and drying it, repeating this process more than once to obtain a melamine sponge-based floating body.

7. The method according to claim 6, characterized in that In step S1, the concentration of dopamine hydrochloride in the mixed solution is (1.5-2.5) g / L, and the amount of TRIS buffer in every 100 ml of the mixed solution is 1-2 ml; Preferably, the concentration of dopamine hydrochloride in the mixed solution is 2 g / L, and the amount of TRIS buffer in every 100 ml of the mixed solution is 1 ml; Preferably, in step S1, the length, width and height of the melamine sponge are (1-2) cm×(1-2) cm×(1-2) cm respectively, the oscillator rate is 145-155 times / minute, and the oscillation time is 11-12 hours; Preferably, the melamine sponge has a length, width and height of 2 cm×2 cm×2 cm respectively, the oscillator rate is 150 times / minute, and the oscillation time is 12 hours.

8. The method according to claim 6, characterized in that In step S2, the concentration of the modified zero-valent copper catalyst in the dispersion is 4-5 g / L; Preferably, the concentration of the modified zero-valent copper catalyst in the dispersion is 5 g / L; Preferably, in step S2, the melamine sponge is soaked for 10 to 20 minutes; Preferably, in step S2, the drying method is drying at 60-80°C.

9. Use of the modified zero-valent copper catalyst prepared by the method according to any one of claims 1 to 4 or the melamine sponge-based floating body according to claim 5 in degrading organic pollutants.

10. The use according to claim 9, characterized in that Use of the modified zero-valent copper catalyst prepared by the method according to any one of claims 1 to 4 or the melamine sponge-based floating body according to claim 5 in degrading organic pollutants in wastewater; Preferably, the organic pollutants include oxytetracycline, tetracycline, rhodamine B, methylene blue, and p-nitrophenol.